"If we want to have a good future, we need to do something about it". Youth, security and imagined horizons in the intercultural Arctic Norway. (3rd July 2021) - Dankertsen, Astri; Pettersen, Elisabeth; Otterlei, Jill-Beth
ABSTRACT: Security is an issue often raised when discussing the Arctic, a region where international relations and tensions between the great powers of the past and present often are taken-for-granted as the traditional scope of dialog. We have chosen to focus on youth in Arctic Norway, their perceived notion of security in their everyday lives, and how this influences their perceived possibilities for the future. We combine human security and ontological security perspectives with the concept of imagined horizons to grasp the discrepancy that we find between how the Arctic is defined from an international relations perspective, and the Arctic that youth in northern Norway understand in their everyday lives. We base the analysis on qualitative interviews with youth of various ethnic backgrounds in the Arctic town Alta in Norway, where we have interviewed them about security, cultural differences, climate change and environmental issues in the Arctic.